2023
DOI: 10.3390/ma17010230
|View full text |Cite
|
Sign up to set email alerts
|

Bronze Age Raw Material Hoard from Greater Poland: Archaeometallurgical Study Based on Material Research, Thermodynamic Analysis, and Experiments

Aldona Garbacz-Klempka,
Marcin Piękoś,
Janusz Kozana
et al.

Abstract: Hoard finds from the Bronze Age have appeared all over Europe, prompting questions about their functions (either as raw materials for recycling or votive objects). The hoard trove of raw materials from Przybysław in Greater Poland is an interesting example of a discovery that is related to the foundry activities of Late Bronze Age and Early Iron Age communities (c. 600 BC). The deposit consists of fragments of raw materials that were damaged end products intended for smelting. The research included the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…This sample also showed elongated precipitates and grain boundary defects. This particular sample's microstructure indicated that the dagger-axe underwent a post-casting heat treatment, resulting in a certain degree of compositional homogenization (see Figures 3d and 4d) [31]. But the specific reason for secondary heating is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…This sample also showed elongated precipitates and grain boundary defects. This particular sample's microstructure indicated that the dagger-axe underwent a post-casting heat treatment, resulting in a certain degree of compositional homogenization (see Figures 3d and 4d) [31]. But the specific reason for secondary heating is unknown.…”
Section: Discussionmentioning
confidence: 97%
“…This article uses EBSD technology to detect and analyze bronze earrings unearthed from the Xindianzi Cemetery, studying their phase, twinning, and grain size and shape. The composition of different phases and inclusions in the alloy was obtained by combining SEM-EDS technology [31]. To further investigate the mechanism of grain formation within the alloy, this study utilized Electron Backscatter Diffraction (EBSD) technology to reconstruct the grain structure of the bronze earrings' X-Y section in detail.…”
Section: Structure and Compositionmentioning
confidence: 99%
“…This article uses EBSD technology to detect and analyze bronze earrings unearthed from the Xindianzi Cemetery, studying their phase, twinning, and grain size and shape. The composition of different phases and inclusions in the alloy was obtained by combining SEM-EDS technology [31].…”
Section: Structure and Compositionmentioning
confidence: 99%